Disconnected dots?: A systematic review of governance challenges for natural resource management. Issue 8 (2nd July 2020) - Potts, Ruth
Abstract : Concerns for the ongoing and increasing degradation of the natural environment worldwide have increased the impetus for action, and development of governance arrangements to support natural resource management. Despite this, several issues around governance still remain as challenges to the success of natural resource management. This study reports the findings of a systematic literature review of 240 papers to better understand how governance challenges manifest spatially, and how they change over time. Also the paper identifies key priority areas for strategic governance reform. This paper reveals that the capacity of natural resource management governance systems internationally is most limited by factors that limit connectivity and collaboration between stakeholders in decision-making processes, and the alignment of vision and objectives across institutions. The paper also reveals clear spatial disparities and temporal changes in the number of studies and governance challenges identified in natural resource management in developing and developed countries.